Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-75564-x
|View full text |Cite
|
Sign up to set email alerts
|

Water strider females use individual experience to adjust jumping behaviour to their weight within physical constraints of water surface tension

Abstract: Different species of water striders match leg speeds to their body sizes to maximize their jump take off velocity without breaking the water surface, which might have aided evolution of leg structures optimized for exploitation of the water surface tension. It is not understood how water striders achieve this match. Can individuals modify their leg movements based on their body mass and locomotor experience? Here we tested if water striders, Gerris latiabdominis, adjust jumping behaviour based on their persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Direct empirical observations provide further explanations. In our previous empirical studies 18,19,27 , we have occasionally observed surface breaking in the smaller species jumping in the laboratory conditions. The breaking occurred in the final moments of jump when the tibia-tarsi section was more-orless vertically oriented (>45 deg to horizontal; example in Fig.…”
Section: Simulation Predictions For the Smaller Water Stridersmentioning
confidence: 77%
See 1 more Smart Citation
“…Direct empirical observations provide further explanations. In our previous empirical studies 18,19,27 , we have occasionally observed surface breaking in the smaller species jumping in the laboratory conditions. The breaking occurred in the final moments of jump when the tibia-tarsi section was more-orless vertically oriented (>45 deg to horizontal; example in Fig.…”
Section: Simulation Predictions For the Smaller Water Stridersmentioning
confidence: 77%
“…Previously published data on several small water strider species 18,19,27,28 , combined with our observations of A. paludum, P. tigrina and G. gigas, match the model predictions but currently there is not enough information on jumping behavior of a variety of species within Gerridae to fully evaluate the central prediction of the model: evolutionary transitions from smaller to larger body size along branches of Gerridae phylogenetic tree will be associated by transitions from surface-tension to drag-involving jumps, especially in habitats of high predation risk where achieving sufficiently high jumping performance is important to evade predatory attacks. Future comparative studies of a variety of small and large water strider species should be able to more precisely determine the body size and midleg length at which the transitions occur, and two subfamilies of water striders, Gerrinae and Ptilomerinae, are promising study taxons because of their wide range of species body sizes (Fig.…”
Section: General Conclusionmentioning
confidence: 99%
“…Water striders, Gerridae, are ideal subjects to study those issues. However, although many studies have taken theoretical approach to understand the physics of water striders [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , the research effort is confined to several small-and medium-sized water striders in spite of a wide range of body mass that spans over two orders of magnitude from less than 5 41 to about 500 mg 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we establish that to achieve a uniform thin lm we should have a simultaneous effect of generating a uniform thin lm over the substrate, and to apply the external force to activate dynamic wetting and this brings about an additional challenge. Also here, nature has its example: water striders are water-walking insects thanks to their non-wetting legs [32][33][34] . These legs are covered with a large number of tiny hair 35 as shown in (Figure S2).…”
Section: Introductionmentioning
confidence: 99%